For an effective political discussion of Human rights - Herrera Rodríguez, Omar S. (2025)
In 2016, Professor Mario Solís Umaña published a book entitled: Justicia Situacional. Racionalidad, normatividad y teoría crítica latinoamericanista, which contains a criticism against the explanation developed by Helio Gallardo on the foundatios of human rights. This work answers the two main criticisms that Solís makes of Gallardo: the accusation of social foundationism and what I will call criticism of the subject that enunciates/produces human rights. In both cases I will show that Solís’ criticism is not very faithful to Gallardo’s text and, furthermore, it is internally inconsistent. I conclude that the discussion on the foundation of human rights proposed by Helio Gallardo continues to be the best theoreticalcomprehensive version to approach this thematicfield.